A thermal-insensitive ultra-broadband metamaterial absorber. (14th December 2020) - Bai, Ningfeng; Zhong, Fuxian; Shen, Jingxuan; Fan, Hehong; Sun, Xiaohan
Abstract: In this paper, a thermal-insensitive ultra-broadband metamaterial absorber (MMA) based on indium tin oxide (ITO) patterns and the SiO2 dielectric substrate is proposed to demonstrate high-temperature stability and excellent absorbability. The surface patterns consist of two different sizes of rectangular split-ring resonators with two gaps in each split-ring. Results from simulation indicate that at the initial temperature of 300 K, the relative absorption bandwidth reaches 83.35%, and the spectrum with absorptivity higher than 90% ranges from 8.00 GHz to 19.43 GHz. Moreover, in the temperature range of 300–700 K, the effective bands remain steady and cover more than 95% of the initial band. The simulation results also verify that the performance of MMA remains stable when exposed to high-intensity incident and high temperature of 500 K. The analysis of the surface current, electromagnetic (EM) field, power-loss density, equivalent circuit, and constitutive EM parameters reveals the mechanisms of thermal-insensitive ultra-broadband. This study expands potential applications of MMAs in conditions with thermal-stable demands.